x2/x+2=10-3x/x+2
x2-3x-10=0
D=b2-4ac=9+4*1*10=49=7
x1=-3-7/2=-5
x2=-3+7/2=5
а)
49 > 0 ⇒ 2 корня
ответ:
б)
484 > 0 ⇒ 2 корня
в)
Сделаем замену:
25 > 0 ⇒ 2 корня
Возвращаемся к замене
x2/x+2=10-3x/x+2
x2-3x-10=0
D=b2-4ac=9+4*1*10=49=7
x1=-3-7/2=-5
x2=-3+7/2=5
а)![\dfrac{x^2}{x+2}=\dfrac{10-3x}{x+2}](/tpl/images/1658/2320/0fab2.png)
49 > 0 ⇒ 2 корня
ответ:![x_1=-5;\ x_2=2](/tpl/images/1658/2320/11f34.png)
б)![\dfrac{x}{x-5}+\dfrac{7x+35}{x^2-25}=2](/tpl/images/1658/2320/d00ce.png)
484 > 0 ⇒ 2 корня
ответ:![x_1=17;\ x=-5](/tpl/images/1658/2320/1e826.png)
в)![x^4-13x^2+36=0](/tpl/images/1658/2320/c9f32.png)
Сделаем замену:![x^2=t](/tpl/images/1658/2320/2aafa.png)
25 > 0 ⇒ 2 корня
Возвращаемся к замене
ответ:![x_1=-3;\ x_2=-2;\ x_3=2; \ x_4=3](/tpl/images/1658/2320/8b19b.png)